2011
DOI: 10.1523/jneurosci.1671-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Memory-Guided Learning: CA1 and CA3 Neuronal Ensembles Differentially Encode the Commonalities and Differences between Situations

Abstract: Memory influences learning, but how neural signals support such transfer are unknown. To investigate these mechanisms, we trained rats to perform a standard spatial memory task in a plus maze and tested how training affected learning and neural coding in two new task variants. A switch task exchanged the start and goal locations in the same environment; whereas an altered environment task contained different local and distal cues. Learning was facilitated in both variants compared to the acquisition of the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 59 publications
1
49
1
Order By: Relevance
“…This finding is in contrast to the independent place code that is often reported for unrelated contexts and also distinct from observation of anti-correlated activity for different behaviors executed within the same space (Bahar et al, 2011; Markus et al, 1995). In our experiment, rats executed the same behaviors in both contexts, though in response to different items.…”
Section: Discussioncontrasting
confidence: 95%
“…This finding is in contrast to the independent place code that is often reported for unrelated contexts and also distinct from observation of anti-correlated activity for different behaviors executed within the same space (Bahar et al, 2011; Markus et al, 1995). In our experiment, rats executed the same behaviors in both contexts, though in response to different items.…”
Section: Discussioncontrasting
confidence: 95%
“…Similarly, Singer et al (2010) reported "path equivalence" of spatial firing patterns of hippocampal neurons as rats traversed separate but parallel segments of routes through a maze. Notably, in these experiments, and in several others in which rats traversed a common path segment while pursuing different trajectories (Frank et al, 2000;Wood et al, 2000;Ferbinteanu and Shapiro, 2003;Smith and Mizumori 2006;Bahar and Shapiro, 2012), some neurons have similar activity associated with the common events, whereas others fire distinctly, thus disambiguating overlapping memories. In monkeys (Hampson et al, 2004) and humans (Quiroga et al, 2005), neurons have been observed that fire similarly in response to stimuli that are visually quite various but are similar in meaning (e.g., a cell that fires to various views of the same famous person and even the name of that person).…”
Section: Discussionmentioning
confidence: 55%
“…These results are reminiscent of previous studies that have shown that multiple exposures can be necessary for CA1 cells to distinguish arenas that differ only by the color of a cue card (Bostock et al, 1991) or remap in response to rotations of proximal and distal cues (Shapiro et al, 1997;Brown and Skaggs, 2002). When a rat must choose between one of several well-learned trajectories through the same space, the different trajectories are encoded by anticorrelated representations in CA1 (Bahar et al, 2011), suggesting that experience may increase the degree to which one representation suppresses competitors.…”
Section: Discussionmentioning
confidence: 99%
“…Remapping has also been observed in a T-maze delayed non-matching to place task where distinct firing patterns were observed between sample trials, where the animal must encode its path, and choice trials, where the animal must remember the correct path (Griffin et al, 2007; also see Hallock and Griffin, 2013). In yet another task, remapping was observed when rats switched between start and goal arms while performing the same spatial memory task in the same maze (Bahar et al, 2011). In parallel with these studies, remapping also occurs when a neutral environment is made aversive by fear conditioning (Wang et al, 2012).…”
Section: What Is the “Memory Code” In The Hippocampus?mentioning
confidence: 99%